Selecting cost effective and policy-relevant biological indicators for European monitoring of soil biodiversity and ecosystem function. (October 2016) - Griffiths, B.S.; Römbke, J.; Schmelz, R.M.; Scheffczyk, A.; Faber, J.H.; Bloem, J.; Pérès, G.; Cluzeau, D.; Chabbi, A.; Suhadolc, M.; Sousa, J.P.; Martins da Silva, P.; et al.
Graphical abstract: Highlights: Eighteen potential indicators selected using a logical sieve. Indicators tested at six European sites across climatic zones. No single indicator sensitive to all differences in land use intensity. Recommended indicators for function are: earthworms; functional genes; and bait lamina. For monitoring of biodiversity all taxonomic groups need to be addressed. Abstract: Soils provide many ecosystem services that are ultimately dependent on the local diversity and belowground abundance of organisms. Soil biodiversity is affected negatively by many threats and there is a perceived policy requirement for the effective biological monitoring of soils at the European level. The aim of this study was to evaluate and recommend policy relevant, cost-effective soil biological indicators for biodiversity and ecosystem function across Europe. A total of 18 potential indicators were selected using a logical-sieve based approach. This paper considers the use of indicators from the 'top down' (i.e. concerned with the process of indicator selection), rather than from the 'bottom up' detail of how individual indicators perform at specific sites and with specific treatments. The indicators assessed a range of microbial, faunal and functional attributes, newer nucleic acids based techniques, morphological approaches and process based measurements. They were tested at 6 European experimental sites already in operation and chosen according to land-use, climatic zone and differences in land management intensity. These were 4 arable sites, one each in Atlantic, Continental, Mediterranean and Pannonian climate zones, and 2 grassland sites, one each in Atlantic and Continental zones. At each site we sampled three replicated plots of contrasting management intensity and, while the treatments varied from site to site, their disturbance effects were quantified in terms of land use intensity. The field sampling and laboratory analysis were standardised through a combination of ISO protocols, or standard operating procedures if the former were not available. Sites were sampled twice, in autumn 2012 and spring or autumn 2013, with relative costs of the different indicators being determined each time. A breakdown of the cost effectiveness of the indicators showed the expected trade-off between effort required in the field and effort required in the laboratory. All the indicators were able to differentiate between the sites but, as no single indicator was sensitive to all the differences in land use intensity, we suggest that an indicator programme should be based upon a suite of different indicators. For monitoring under the European climatic zones and land uses of this study, indicators for ecosystem functions related to the services of water regulation, C-sequestration and nutrient provision would include a minimum suite of: earthworms; functional genes; and bait lamina. For effective monitoring of biodiversity all taxonomic groups would need to be addressed.